2011
DOI: 10.1159/000334718
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the Risks and Benefits of Genomic Data Sharing: Genome Research Participants’ Perspectives

Abstract: Background: Technological advancements are rapidly propelling the field of genome research forward, while lawmakers attempt to keep apace with the risks these advances bear. Balancing normative concerns of maximizing data utility and protecting human subjects, whose privacy is at risk due to the identifiability of DNA data, are central to policy decisions. Research on genome research participants making real-time data sharing decisions is limited; yet, these perspectives could provide critical information to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(143 citation statements)
references
References 43 publications
4
134
0
Order By: Relevance
“…This may have been influenced by their reported trust in medical professionals, 14 which could have contributed to a greater perception of informed consent than previously observed in pediatric cancer 20 and biobanking studies. 21 There was little disagreement over the benefits of study participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have been influenced by their reported trust in medical professionals, 14 which could have contributed to a greater perception of informed consent than previously observed in pediatric cancer 20 and biobanking studies. 21 There was little disagreement over the benefits of study participation.…”
Section: Discussionmentioning
confidence: 99%
“…Interviews lasted ∼45 minutes and were transcribed verbatim. More details on the interview and development of the questionnaire can be found in Oliver et al 14 The autism and epilepsy studies also enrolled family members to serve as matched case controls (n = 25). All family members were randomly assigned to the same experimental ICD (treated as distinct consent choices), and all family members present typically contributed to 1 structured interview.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Also, previous work has shown that participants were generally more restrictive in their hypothetical preferences than in their actual response. 64 Those in one study were 'perplexed by the need for re-consent, feeling that they had already provided such consent in the original wording.' 65 This contrasts with studies where actual participants and the public, in hypothetical situations, preferred re-consent for each new use.…”
Section: Challenges For Re-consentmentioning
confidence: 99%
“…Evidence regarding public awareness of confidentiality risks is conflicting (Kaufman et al, 2009;Brothers et al, 2011;Oliver et al, 2011;Trinidad et al, 2012;Rogith et al, 2014). A survey study (N = 1041) about consent to a hypothetical biobank found that 75% of participants disapproved of using their genetic material because of security concerns (Kerath et al, 2013).…”
mentioning
confidence: 99%